Preparação e caracterização de compósitos de polietileno de alta densidade com casca de arroz e oxibiodegradante para a produção de tubetes florestais - Costa, Cristiano Cunha (2018)
The use of agricultural waste, such as rice husk (RH), for the production of cheap and eco-friendly polymer composites has emerged as a promising field of interest. The aim of this work was the preparation of high-density polyethylene (HDPE)-based composites reinforced with rice husk and an organic pro-oxidant (EG) for the production of seedlings tubes. Photodegradation and degradation tests in simulated soil were performed for 90 and 180 days in order to study the decomposition of these composites. The SEM and OM images suggest that degradation of the composites samples was more extensive than the pure HDPE samples, probably because the composites present intense light absorption in the UV range, facilitating the degradation process even before biodegradation begins. In addition, after introducing RH particles in the polymeric matrix, the mechanical tensile and flexural properties, experienced significant changes, suggesting that the RH particles were homogeneously dispersed throughout the polymer matrix. In addition, it was possible to identify microorganisms with polyethylene biodegradation activity, such as Aspergillus niger, Penicillium spp., Trichoderma spp., Rhizopus spp. The results have demonstrated that HDPE, RH, and EG are attractive materials for the design of polymeric composites for the production of seedlings tubes with excellent mechanical properties, being, also, easily decomposed in the environment once discarded.